2023
DOI: 10.1039/d3ta02382f
|View full text |Cite
|
Sign up to set email alerts
|

UV-robust and efficient perovskite solar cells enabled by interfacial photocatalysis suppression and defect passivation

Abstract: Interfacial photocatalysis of metal oxide electron transport layers (ETLs), especially TiO2, in organometal halide perovskite solar cells (PSCs) have detrimental effects on device stability. Herein, a UV absorber, 4,4'-Oxydibenzoic acid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This number is lower than that of the 8.84 × 10 15 cm –3 measured for the control film. The decreased trap density in the CHX-contained device shows that the addition of CHX improves the quality of perovskite films and successfully passivates perovskite defects. , Impedance measurements are carried out in the dark at open-circuit voltage. The target device’s arc is obviously much bigger than that of the control device, according to the Nyquist plots in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…This number is lower than that of the 8.84 × 10 15 cm –3 measured for the control film. The decreased trap density in the CHX-contained device shows that the addition of CHX improves the quality of perovskite films and successfully passivates perovskite defects. , Impedance measurements are carried out in the dark at open-circuit voltage. The target device’s arc is obviously much bigger than that of the control device, according to the Nyquist plots in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…[49] It can be found that the value of α was increased from 0.993 (control) to 0.995 (FePP), indicating that FePP enhanced the carrier extraction and transport ability of HTL, thereby inhibiting recombination of interface carriers. Similarly, V OC and the logarithm of light intensity are plotted to obtain Figure 4b, and linear fitting was performed according to formula (5) [50] V…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, polycrystalline perovskite films are typically prepared via solution processing methods, which inevitably introduce defects such as uncoordinated Pb 2+ and halide ion (I – ) vacancies at the grain boundaries and interfaces between the perovskite layer and the electron-transporting layer (ETL). , Numerous studies have engaged to improve the crystallinity and morphology of the perovskite films and passivate defects on the surface or at the interface via various strategies, including additive implementation, , antisolvent engineering, and interface adjustment. , Particularly, interfacial engineering with functional semiconductors has been proved to be an effective approach for enhancing the PSCs’ photovoltaic properties along with facilitating the transportation of the charges, reducing defect density, and suppressing the recombination of the carriers, thereby promoting the crystal growth of the perovskite film and improving the photovoltaic performance of the solar cells. Among them, nanomaterial nitrogen-doped graphene quantum dots (N-GQDs) can act as an effective interface modulation reagent for efficient PSCs, which is utilized to ameliorate the following perovskite film quality and facilitate charge-transfer kinetics as well. Bian et al embedded N-GQDs on the surface of γ-CsPbI 3 -based PSCs.…”
Section: Introductionmentioning
confidence: 99%